2016
DOI: 10.1371/journal.pone.0157997
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Exposure Differentially Alters Monolayer versus Microtissue MCF-7 Human Breast Carcinoma Cultures

Abstract: The development of three-dimensional (3D) cultures is increasing, as they are able to provide the utility of in vitro models and the strength of testing in physiologically relevant systems. When cultured in a scaffold-free agarose hydrogel system, MCF-7 human breast carcinoma cells organize and develop into microtissues that contain a luminal space, in stark contrast to the flat morphology of MCF-7 two-dimensional (2D) monolayer cultures. Following exposure to 1nM E2, expression of typical estrogen-responsive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 26 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…Subsequently, we set out to identify suitable inducible ERα target genes that could serve as candidate ERα activity reporters. We selected 5 potential candidates for our reporter cell lines-based transcriptomics information from our own work and other studies: CCND1 , GREB1 , PGR , PTGES , and TFF1 ( Frasor et al , 2003 ; Lin et al , 2004 ; Moerkens et al , 2014 ; Vantangoli et al , 2016 ; Zhang et al , 2011 ). Except for CCND1, these genes have previously been described as primary ERα transcriptional target genes rather than indirect or secondary targets, because they contain EREs in their regulatory regions ( Berry et al , 1989 ; Deschênes et al , 2007 ; Frasor et al , 2008 ; Lin et al , 2004 ; Sun et al , 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we set out to identify suitable inducible ERα target genes that could serve as candidate ERα activity reporters. We selected 5 potential candidates for our reporter cell lines-based transcriptomics information from our own work and other studies: CCND1 , GREB1 , PGR , PTGES , and TFF1 ( Frasor et al , 2003 ; Lin et al , 2004 ; Moerkens et al , 2014 ; Vantangoli et al , 2016 ; Zhang et al , 2011 ). Except for CCND1, these genes have previously been described as primary ERα transcriptional target genes rather than indirect or secondary targets, because they contain EREs in their regulatory regions ( Berry et al , 1989 ; Deschênes et al , 2007 ; Frasor et al , 2008 ; Lin et al , 2004 ; Sun et al , 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…The CCND1 promoter does not contain a classical ERE, however, estrogen-responsive transcription is mediated via a c-Jun/c-Fos/ERα-complex ( Cicatiello et al , 2004 ). These targets are described in literature to be upregulated after E2 exposure and they are (in)directly linked to cell proliferation ( Amiry et al , 2009 ; Butt et al , 2005 ; Cenciarini and Proietti, 2019 ; Frasor et al , 2003 ; Lin et al , 2004 ; Rae et al , 2005 ; Vantangoli et al , 2016 ). To verify whether these targets are indeed inducible by E2 in our MCF7 cell line, cells were exposed to 1 nM E2 up to 24 h, showing different temporal dynamics of mRNA expression ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…These transcriptional changes support other studies, which showed that estrogenic compounds promote EMT in ER+ breast cell lines. 3,35,41,42 Cells that undergo EMT adopt an invasive phenotype. In scratch assays, MCF7 migration increased upon exposure to E2.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Surprisingly, ERα mRNA levels were insensitive to hypoxia (1% O 2 via hypoxic chamber) in 3D whereas in 2D, a decrease in ERα transcription activity was reported. [170] In another study, the exposure of MCF-7 breast cancer spheroids and MCF-7 monolayer cells to estradiol showed similar expression profile for estrogen-regulated transcription targets (progesterone receptor (PGR); amphiregulin (AREG) and PDZ containing domain 1 (PDZK1)); however, they showed differentially activated cell-cell interactions pathways [171], which was attributed to differences in cellular differentiation in 2D and 3D cultures. In our own study [172], sizecontrolled 3D microtumors generated using hydrogel microwells of defined diameter (150 and 600 μm) showed differential microtumor size-dependent ERα expression.…”
Section: Comparative Studies Between 2d and 3d Modelsmentioning
confidence: 99%